الاعجاز القرآني في ضوء المعطيات المعرفية المعاصرة - الفتلاوي, محمد كاظم; شكر, نصير علي موسى (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The Qur’anic miracle is one of the important topics of Qur’anic sciences, as a number of issues depend on it. Therefore, this issue has been the subject of research and the focus of attention of scholars and researchers, as dozens of books and research have been written on this subject. These researches and studies varied in their contents. Some of them dealt with the rhetorical miracle, and some of them examined the scientific, numerical, and metaphysical miracles and other aspects of the Qur’anic miracle. In this research, the researcher attempts to highlight the “educational miracle,” which could be one of the contemporary aspects of the Qur’anic miracle, as all the educational theories developed by Western philosophers in the field of human education, through which they hoped to bring man to a state of psychological stability and spiritual transcendence, have failed, so today’s human being has returned. More worrying and turbulent, as educational theories have not succeeded in answering humanity’s greatest questions, and what is noticeable is that these theories conflict with each other and intersect, and what they adopted yesterday, they came today to refute, and this is what we see clearly in the West’s entry into the post-modern stage. On the contrary, we note that the educational contents of the Qur’an are consistent. It answers man's major universal questions, which gives man a state of tranquility, and he knows, and is even certain, where he came from, what his role is now, and where he is going.